Дослідження динамічних навантажень рами фронтального навантажувача з використанням комп’ютерних 3D моделей у середовищі Siemens NX - Щербак, О. В.; Сумінов, А. В.; Хачатурян, С. Л.; Sherbak, О.; Suminov, А.; Khachaturyan, S. (ЦНТУ, 2023)
У статті запропоновано нове рішення з проведення аналізу міцності рами фронтального навантажувача на стадії проєктування за допомогою комп’ютерних 3D моделей у середовищі Siemens NX. Даний метод дозволяє не створювати нову модель рами в металі у натуральну величину для проведення випробувань. Відповідно до запропонованого методу достатньо виконати масштабовану спрощену модель майбутньої рами, провести випробування на міцність та запропонувати конструктивні зміни щодо розробки раціональних параметрів. Такий метод дозволяє суттєво скоротити витрати на матеріали, виробництво та час виготовлення нових виробів. When designing new construction and road machines, a variety of CAD and CAE computer programs are used. The designer has the ability to set certain strength properties of the future structure using finite element calculations, and after the first prototype is made, the moment comes when it needs to be tested for loads applied during technological operations to confirm the preliminary strength calculations. The goal of this work is to compare the test results of 3D models of two load-bearing systems of the T-156B loader, one of which is the original and the other a fivefold reduced copy. The result of the comparison is a reduction factor, the calculation of which will allow us to determine how and how many times the load is reduced when scaling 3D models. Previous work on this topic was done in the Ansys calculation complex, but the long process of calculating the task, importing, and complex process of configuring the model forced us to switch to a faster Siemens NX software complex. This software package has a clear and simple interface while performing calculation tasks much faster than Ansys. In this work, similarity coefficients were calculated for two more common cases of forklift operations: moving a full bucket over an uneven surface and colliding with an obstacle while filling the bucket. Thus, knowing these coefficients, it can be assumed that when modeling a new load-bearing system, by making a reduced copy of it in the appropriate scale and testing it for loading by means of computer modeling, or by conducting field tests, it is possible to calculate what loads will affect the model with natural dimensions. The article proposes a new solution for analyzing the strength of load-bearing systems at the design stage using the theory of similarity. This method makes it possible not to create a full-size model of a new loadbearing system (frame) in metal for testing. In accordance with the proposed method, it is enough to make a scaled simplified model of the future load-bearing system (frame), conduct strength tests and, in accordance with the similarity coefficient, calculate what loads will affect the full-size load-bearing system. This method can significantly reduce the cost of materials, production, and manufacturing time for new products.
Study of Dynamic Loads of the Front Loader Frame Using 3D Computer Models in the Siemens NX Environment
Keywords: міцність; рама; навантаження; випробування; 3D модель; динаміка; тривимірне комп’ютерне моделювання; Siemens NX; strength; dynamics; three-dimensional modeling; Siemens NX; similarity theory; design